SITUATIONAL AWARENESS: APPLICATION AREAS OF COMPUTER ENGINEERING AND ARTIFICIAL INTELLIGENCE - Денисюк, Олександр (SWorldJournal, 2024)
The paper is devoted to the consideration of situational awareness in such areas of application as computer engineering and artificial intelligence. Situational awareness is becoming more important in modern life, where the high pace, interdependence of e